UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN SELADA ROMAINE (Lactuca sativa var. Longifolia) DAN DAUN SELADA KERITING (Lactuca sativa var. Crispa) BESERTA IDENTIFIKASI BEBERAPA SENYAWA ANTIOKSIDAN - Maria Ulfah; Ady Laksono Putro; Efa Erfiana Safitri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2019)
ABSTRACTFree radicals are suspected as triggers of various degenerative diseases. Antioxidants are compounds that can counteract free radicals. This study aims to determine the antioxidant activity by DPPH method and analyze the active compounds contained in romaine lettuce extract (Lactuca sativa var Longifolia) and lactuca sativa var Crishpa lettuce extract (Lactuca sativa var Crishpa). Romaine lettuce and and lactuca sativa var Crishpa was done extraction with a maceration method using 70% as ethanol solvent. The concentration of extract used was 12.5; 25; 50; 100; 200 and 400 ppm and vitamin C concentrations as comparison was 0.5; 1; 1.5; 2; 2,5 and 3 ppm tested its antioxidant activity by DPPH method by spectrophotometry visible, until IC50 value was obtained. The identification of the active compound was performed by phytochemical screening and Thin Layer Chromatography (TLC). The results showed that romaine lettuce has IC50 value of 151,1515 ppm and lactuca sativa var Crishpa has IC50 value of 183,7560 ppm and vitamin C value was 1,7005 ppm. The chemical compounds contained in romaine ethanol extract and lactuca sativa var Crishpa lettuce extract are alkaloids, phenols and flavonoids.Keywords: Antioxidant, DPPH, IC50, TLC, Romaine, Lactuca sativa var Crishpa